Research on the programming language for proxy re-encryption - Mang SU; Yan YU; Bin WU; Anmin FU (Tongxin xuebao)
The programming language for proxy re-encryption(PLPRE) based on domain specific language(DSL) was proposed,which was similar to the matical description and was adopt to describe the proxy re-encryption directly.The algorithm designer could describe the algorithm conveniently and quickly by PLPRE,and obtain the programming code for computer.Firstly,the grammar of PLPRE was presented,including the definitions of the keyword and programming logic,then the ACC-PRE algorithm was described by PLPRE as an example.Secondly,the PLPRE parser was realized by ANTLR.Finally,the comparisons between the PLPRE and the related work were made.By using the PLPRE,user does not need to pay attentions to data structure or memory allocation.It is suitable for the cryptography experts who is not familiar with the programming.Thus,PLPRE will decrease the deviation between the design and implement for PRE.